Visualizing Crisis Management: Crisis Experience, Concern, and Training in China - Parnell, John A.; Crandall, William “Rick”; Zhang, Long; Lin, Yuanyuan (Journal of Comparative International Management)

(untitled) (Management Futures, 2023)
China’s increasing international prominence has prompted additional research on how Chinese firms manage organizational crises. The purpose of this paper is to identify patterns of concerns and experiences with crises in China. We report on a survey of 105 managers and non-managers in China about their experience and concern with crises in their firms. Our analysis underscores three key findings. First, one's concern about a crisis is strongly associated with one's experience involving that crisis. Second, views about crisis experience and concern differ between employees in state-owned enterprises (SOEs) and non-SOEs. Finally, despite these differences, perspectives on crisis training among SOE and non-SOE firms are similar. This paper augments the literature by identifying relationships among crisis experience, crisis concern, and training in Chinese organizations.